Technical SEO as Web Systems Engineering for Crawlability, Indexability, and Platform Performance - Samuel N. Kato (Kalam Practica Media, 2026)
Technical search engine optimization has increasingly shifted from keyword-oriented optimization toward web systems engineering, where crawlability, indexability, rendering efficiency, structured data, and performance architecture determine whether digital platforms can be discovered, processed, and served effectively by search systems. This study examined the effect of technical SEO engineering indicators on digital platform performance using a simulated panel dataset of institutional and commercial websites. The study used a balanced panel design covering 12 websites observed monthly across 12 periods, producing 144 website-month observations. The dependent variable was organic visibility performance, measured as a composite score of impressions, indexed pages, organic clicks, and average ranking stability. Independent variables included crawl efficiency, index coverage, Core Web Vitals pass rate, structured data validity, mobile usability, internal link depth, sitemap health, canonical consistency, and server response time. Fixed-effects and random-effects panel regressions were estimated, followed by Hausman testing, variance inflation diagnostics, and robustness checks using lagged technical indicators. Fixed-effects estimation showed that index coverage, Core Web Vitals pass rate, structured data validity, and crawl efficiency had positive and statistically significant effects on organic visibility performance. Server response time had a negative significant effect. The optimized technical SEO configuration increased the mean visibility score from 61.84 to 78.26 over the observation window. Technical SEO can be conceptualized as a web systems engineering approach because search visibility depends on measurable infrastructure, architecture, and performance conditions. The findings support integrating technical SEO audits into engineering governance for digital platforms.